DEVELOPMENT OF OIL BIOREMEDIATION RESEARCH ON MARINE ENVIRONMENT IN INDONESIA - Yeti Darmayati (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Indonesian marine environment is one of the most vulnerable waters from oil pollution in the world. Therefore, a hard effort to minimize oil pollution impact is really needed. Physical and chemical approaches have been already popular to combat oil pollution; one of the other promising techniques is bioremediation, the use of microorganism to detoxify or remove pollutants. Research and application of bioremediation on soil environment has been started in Indonesia; however, in marine environment it is still need to be studied due to more complicated aspects and also difficulties. Development of bioremediation study on marine environment in Indonesia has been started from enumeration, isolation and identification of oil degrading (hydrocarbonoclastic) bacteria. Researches on taxonomic and functional genes have been conducted. Biostimulation and bioaugmentation studies are ongoing research which conducted from laboratory scale and microcosm scale to field experiment (sand column). To have a manual or guidelines on conducting bioremediation in marine environment is not easy and still many steps have to be done. Several aspects concerning with this study such as the diversity of polluted sites characteristic, oils characteristic, oceanographic conditions and engineering has to be studied comprehensively.